AP biology for dummies - Mikulecky, Peter 4 0 (Peter J.)16; Gilman, Michelle Rose,;Peterson, Brian; 5 (Hoboken, New Jersey : Wiley, 2008)
Presents hundreds of tips and strategies designed to help students in Advanced Placement biology classes, and covers molecules and cells, organisms and populations, DNA, review tests and answers, and helpful lists grouping ten variables on a number of topics.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Examinations;Study guides. -- Biology;Advanced placement programs (Education) -- 20 -- Study guides; 20; 2